Pengaruh Shalwar Kameez dan Tagar #DoNotTouchMyClothes Sebagai Simbol Feminisme Digital di Afghanistan - Aenuna, Nisryna Lintang (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
The return of Taliban rule in Afghanistan was followed by the issuance of regulations by the Taliban restricting women's freedom of expression, one of which is the obligation for Afghan women to wear the burqa in their daily lives. This has sparked a digital feminist movement advocating for women's freedom of dress in Afghanistan, using the hashtag #DonNotTouchMyClothes alongside posts of women wearing Shalwar Kameez. The digital feminist content posted on Instagram, X, and TikTok was analysed using qualitative methods, employing a discourse analysis approach and drawing on journal literature. Through postcolonial feminist theory, the performativity of gender, and cyber feminism, the author explains the influence of digital feminist content in terms of its widespread reach among global citizens. The use of the hashtag #DonotTouchMyClothes and the posting of Shalwar Kameez are forms of resistance against Taliban regulations that do not align with the norms and identities of Afghan women that have existed before these regulations. The conclusion drawn from this research is that digital feminism not only requires many allies to achieve success but also necessitates direct volunteer assistance on-site and material support to control and achieve tangible success in social life effectively.